September 11 and the Rise of Necessity Self-Employment among Mexican Immigrants - Chunbei Wang; Magnus Lofstrom (Institute of Labor Economics (IZA), 2019)
Since the September 11 attacks (9/11), the U.S. has seen a tightening of immigration policies. Previous studies find that stricter immigration enforcement has the unintended effect of pushing undocumented immigrants into self-employment. This paper builds on the literature to better understand the changes in the types of self-employment among Mexican immigrants triggered by the tightened immigration enforcement after 9/11. Using a difference-in-differences approach, and the recently developed measures by Fairlie and Fossen [2018] to distinguish between necessity and opportunity self-employment, we find that both necessity and opportunity self-employment increased among Mexican immigrants after 9/11. However, the effect is most prominent on necessity self-employment, consistent with the hypothesis that they are pushed into self-employment as a survival alternative.
Keywords: J15; L26; 330; mexican immigrants; self-employment; 9/11; tightened immigration policies; necessity